Detecting taxonomic and phylogenetic signals in equid cheek teeth: towards new palaeontological and archaeological proxies. Issue 4 (5th April 2017) - Cucchi, T.; Mohaseb, A.; Peigné, S.; Debue, K.; Orlando, L.; Mashkour, M.
Abstract : The Plio–Pleistocene evolution of Equus and the subsequent domestication of horses and donkeys remains poorly understood, due to the lack of phenotypic markers capable of tracing this evolutionary process in the palaeontological/archaeological record. Using images from 345 specimens, encompassing 15 extant taxa of equids, we quantified the occlusal enamel folding pattern in four mandibular cheek teeth with a single geometric morphometric protocol. We initially investigated the protocol accuracy by assigning each tooth to its correct anatomical position and taxonomic group. We then contrasted the phylogenetic signal present in each tooth shape with an exome-wide phylogeny from 10 extant equine species. We estimated the strength of the phylogenetic signal using a Brownian motion model of evolution with multivariate K statistic, and mapped the dental shape along the molecular phylogeny using an approach based on squared-change parsimony. We found clear evidence for the relevance of dental phenotypes to accurately discriminate all modern members of the genus Equus and capture their phylogenetic relationships. These results are valuable for both palaeontologists and zooarchaeologists exploring the spatial and temporal dynamics of the evolutionary history of the horse family, up to the latest domestication trajectories of horses and donkeys.